2002
DOI: 10.1007/s11661-002-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation-disclination model of heterogeneous martensite nucleation in transformation-induced-plasticity steels

Abstract: A dislocation-disclination model is proposed, describing the heterogeneous nucleation of an embryo of hcp martensite at a tilt grain-boundary segment containing some extrinsic dislocations. The total energy gain due to hcp embryo nucleation is analyzed in detail, and the existence of both the equilibrium and critical embryo sizes under varying external conditions (temperature and shear stress) is shown. Depending on the external conditions, these characteristic embryo sizes may vary in wide ranges. So, the equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…It is possible to increase the transformation range of a TRIP steel alloy by varying alloy composition. While alloy compositions were carefully selected according to the literature, the effects of the numerous alloying elements on the transformation are not yet properly understood and have not been fully characterized [13][14][15]. The alloy used in this application will also be required to display very good mechanical properties, thus again restricting alloy design to high tensile warm rolled alloys.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to increase the transformation range of a TRIP steel alloy by varying alloy composition. While alloy compositions were carefully selected according to the literature, the effects of the numerous alloying elements on the transformation are not yet properly understood and have not been fully characterized [13][14][15]. The alloy used in this application will also be required to display very good mechanical properties, thus again restricting alloy design to high tensile warm rolled alloys.…”
Section: Introductionmentioning
confidence: 99%
“…When the martensite transformation temperature M s is just a little higher than room temperature, the stress-induced c!e transformation easily occurs with only a small mechanical driving force that is equal to the ratio of the stacking fault energy of austenite (E sf ) to the energy associated with Shockley partials [1][2][3]. According to the composition design to obtain a good shape memory effect [6][7][8][9], it was found that the alloy having the lowest stacking fault energy and single austenite phase has the best shape memory effect. Fe-Mn-Si-Cr-Ni alloys do the best among the ironbased shape memory alloys, whose corresponding composition of the alloy is located in the c-phase zone near the phase line between the c and the c+e phase zone and the triple point connected with a, c and e zones in the Schaeffler diagram where a denotes the ferrite [7].…”
Section: Introductionmentioning
confidence: 99%